2015
DOI: 10.1038/npjbiofilms.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of a biofilm-specific reaction rate: kinetics of bacterial urea hydrolysis in a biofilm

Abstract: Background/Objectives:Biofilms and specifically urea-hydrolysing biofilms are of interest to the medical community (for example, urinary tract infections), scientists and engineers (for example, microbially induced carbonate precipitation). To appropriately model these systems, biofilm-specific reaction rates are required. A simple method for determining biofilm-specific reaction rates is described and applied to a urea-hydrolysing biofilm.Methods:Biofilms were grown in small silicon tubes and influent and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
(21 reference statements)
1
22
0
Order By: Relevance
“…With the aid of modern software, reactive transport modelling enables the analysis of coupled physical, chemical, and biological processes in defined systems 193 . For instance, by using laboratory experiments to grow E. coli MJK2 biofilms in the presence of urea and by measuring the characteristics of the developed biofilm, Connolly et al 194 used COMSOL Multiphysics software (a finite element framework; COMSOL Inc., Burlington, MA, USA) to determine the kinetic coefficients of bacterial urea hydrolysis in the biofilm. Determination of biofilm-specific reaction rates can provide accurate microscale modelling of biofilm systems and, therefore, have potential applications in systems such as urethral catheters 195 .…”
Section: Multidisciplinary Approach To Managementmentioning
confidence: 99%
“…With the aid of modern software, reactive transport modelling enables the analysis of coupled physical, chemical, and biological processes in defined systems 193 . For instance, by using laboratory experiments to grow E. coli MJK2 biofilms in the presence of urea and by measuring the characteristics of the developed biofilm, Connolly et al 194 used COMSOL Multiphysics software (a finite element framework; COMSOL Inc., Burlington, MA, USA) to determine the kinetic coefficients of bacterial urea hydrolysis in the biofilm. Determination of biofilm-specific reaction rates can provide accurate microscale modelling of biofilm systems and, therefore, have potential applications in systems such as urethral catheters 195 .…”
Section: Multidisciplinary Approach To Managementmentioning
confidence: 99%
“…First-order relationships have been successfully used to describe microbial ureolysis (Lauchnor et al, 2015;Connolly et al, 2015). Indeed, while the Michaelis-Menten model has been used when evaluating ureolysis, studies of ureolysis-based carbonate precipitation have demonstrated that the first-order ureolysis rate model fits well for urea concentrations of 330 mM or below (Lauchnor et al, 2015;Connolly et al, 2015), which is the concentration range used in this study. The change in urea concentration was determined according to Eqs.…”
Section: Kinetics Of Ureolysis and Caco 3 Precipitationmentioning
confidence: 97%
“…Quantitative descriptions of urine flow and urine chemistry can be obtained using mathematical modeling along with the simulation of biofilm development and mineral precipitation similarly to work done in the development of engineered biomineralization technologies [32][33][34][35][36][37].…”
Section: Investigation Of Struvite Stone Formation Using In Vitro Andmentioning
confidence: 99%
“…An example of a user-friendly modeling program that can be used to model reactive transport is COMSOL Multiphysics® software (a finite element framework, COMSOL Inc., Burlington, MA, USA). Connolly et al [35] used this software to estimate biofilm-specific kinetics of ureolytic biofilms (E. coli MJK2) in flow systems. Estimating ureolysis biofilmkinetics along with other tools to characterize biofilms (e.g.…”
Section: Investigation Of Struvite Stone Formation Using In Vitro Andmentioning
confidence: 99%